Near pure surface uplift of the Argentine Frontal Cordillera: Insights from (U-Th)/He thermochronometry and geomorphic analysis - Hoke, Gregory D. (2015)
Apatite (U-Th)/He thermochronology from palaeosurface-bounded vertical transects collected in deeply incised river valleys with >2 km of relief, as well as geomorphic analysis, are used to examine the timing of uplift of the Frontal Cordillera and its relation to the evolution of the proximal portions of the Andean foreland between 32° and 34°S latitude. The results of apatite (U- Th)/He (AHe) analyses are complex. However, the data show positive age-elevation trends, with higher elevation samples yielding older AHe ages than samples at lower elevation. Slope breaks occur at c. 25 Ma in both profiles, separating very slow cooling and or residence within a partial retention zone (slope of c. 10 m/Myr) at the highest elevations from a slope of c. 60-100 m/ Myr cooling rate at lower elevations. The older AHe ages suggest either (1) minimal burial of the Frontal Cordillera and/or (2) significant pre-middle Miocene local relief. Geomorphic analysis of the adjacent, east-draining Río Mendoza and Río Tunuyán catchments reveals a glacial imprint to the landscape at elevations above 3000 m, including greater channel steepness and lower profile concavities developed during glacial erosion. Detailed analysis of headwall heights provides evidence of ongoing rock uplift along the entire eastern flank of the Frontal Cordillera and in the eastern flank of the Principal Cordillera south of the slab dip transition.